A Study on Energy Efficiency in Wireless Multimedia Sensor Networks - Arafat Şentürk; Zehra Karapınar Şentürk (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Wireless Multimedia Sensor Networks (WMSNs) consist of cheap sensors which transmit real time multimedia data to each other or to a sink. An audio and a visual information may exist in a single device. besides, WMSNs are able to store real time data after gathering it from several sensors. But since both the size of transferred data is big and the difficulties to reach the areas where WMSNs are used, network lifetime of WMSNs and their energy become a vital requirement. Using energy in an efficient way is also necessary for a network not to loose its functionality. What kind of solutions are considered in the literature for WMSNs and its analysis are given ın this paper. First, where the WMSNs are used is shortly mentioned and then, the studies related to energy efficiency are investigated.